Maternal mortality due to thermal injury in pregnancy - Mehta, Harsh Rajeev; Wasadikar, Pravinkumar; Tidke, Abasaheb (International Journal of Scientific Reports, 2021)
Background: Human physiology is altered during pregnancy and adds further stress to systems that are already modified. Mother and foetus are placed at increased risk by burns injury, which is often associated with a high rate of both fetal and maternal mortality and morbidity. Methods: All pregnant patients with burns injuries admitted at our tertiary hospital under department of general surgery from June 2017 to May 2019. This study included 20 pregnant patients with burns injury. Results: Of the total 20 cases, the percentage of TBSA varied from 5% to 100%. There were 19 cases of accidental burns and one case of homicidal burns. There were 11 preterm deliveries of which two stillbirths and nine spontaneous abortions occurred. In all, ten out of twenty mothers died after severe burns amounting to total maternal mortality at 50%. Conclusions: Burns during pregnancy demands special management and requires early and adequate resuscitation with the use of a limited choice of antibiotics and local antibacterial agents. Early surgical intervention and a special obstetric protocol are required in the management of these patients to improve maternal outcome.